Eksplorasi Peran Ontologi Dalam Pengembangan Penelitian Pendidikan Inklusif Dan Berkeadilan - Nursyeha, Muhammad Iksan Fahmi (Peneliti.net, 2025)
Minorities who have differences are often a concern in the world of education, especially because of the negative and discriminatory treatment they often receive in the school environment, either through teachers or peers. This situation shows the importance of implementing inclusive education as a system that provides learning rights fairly and equally to all learners without discrimination. Inclusive education not only emphasizes accessibility, but also a deeper understanding of diversity through a philosophical approach. This article aims to examine the importance of an ontological approach in inclusive education research. This approach allows for a deeper understanding of the reality of diversity in schools and opens up space for the exploration of ways to overcome discrimination. The research method used is a literature study, by analyzing literature from various relevant sources. The results show that ontology in philosophy of science can be a strong conceptual framework for understanding and solving problems in inclusive education research, especially in designing strategies that are responsive to the needs of minority students.